Psychometric Properties of the Malay Version-Revised Five-To-Fifteen (5-15R) Parental Questionnaire (Malay-5-15R) - Jusoh, Masnira; Md Yusoff, Nurul Najwa (International Journal of Allied Health Sciences, 2025)
Introduction: There is a limited available or published questionnaire that suits the Malay-speaking population to screen or assess child development such as physical development, behavior, emotions, cognition, communication skills, or socialization. Professionals that involve children with behavior and developmental needs other supporting assessment for the diagnosis of the children, and one of them is to use questionnaires that can be filled by the teachers and parents as a screening tool. Thus, the current study focuses on other psychometric properties to validate the initial version of Malay-5-15R. Methods: The initial version of the Malay-5-15R questionnaire has been content validated by the experts from the previous study. The validity of Malay-5-15R was further examined by conducting 1) pre-testing and face validity; 2) proofreading; and 3) pilot study. Objective: The aims of the current study are; to pre-test the Malay version of Five-to-Fifteen-Revised (Malay-5-15R); to determine the face validity of the Malay-5-15R; to examine the internal consistency reliability of the Malay-5-15R; to examine the test-retest reliability of the Malay-5-15R; and to examine the convergent and divergent validity of the Malay-5-15R (by using inter-item correlation) within and between domains respectively. Results: The initial version of the Malay-5-15R questionnaire appeared to be understandable for pre-testing. Pilot study was conducted to the two groups of population: parents with normal developmental children and parents having secondary diagnosis children. Results showed that the initial version of the Malay-5-15R exhibited sufficient internal consistency (? > 0.93). The initial Malay-5-15R version was shown to have an excellent coefficient of stability with a correlation coefficient value of 0.98. For convergent validity, most of the Malay-5-15R items has a significant correlation with items in the sub-domains with r-values of greater than 0.30 (p < 0.05) . While for the divergent validity, about 99% of the items were correlated with r-values below the permitted value of 0.85 (p < 0.05). Conclusions: This study concluded that the Malay 5-15R questionnaire has a good face validity, internal consistency reliability, test-retest reliability, convergent validity, and divergent validity which are the parts of psychometric properties. Therefore, it shows that the Malay 5-15R questionnaire is valid and reliable to be used in the Malay-speaking population.